The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.53730/ijhs.v6ns3.7763
|View full text |Cite
|
Sign up to set email alerts
|

Detection of virulence genes and antimicrobial susceptibility of salmonella spp isolated from diarrheal human in wasit province, Iraq

Abstract: This study aimed to isolate Salmonella species from diarrheal human and to determine the antimicrobial susceptibility and virulence-associated genes. A total of 145 human stool samples were from  Wasit province, during the period from November 2018 to August 2019. The isolates were identified according to colony morphology, Gram stain, biochemical, Analytical profile index strip (Api-20E) and serotyping. The antimicrobial susceptibility test was done by utilizing the VITEK-2 Compact system and a disc diffusion… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Research addressing the issue of antibacterial resistant bacteria in Iraq includes many works in the recent years. Most researchers focused on bacterial species such as: Salmonella species [36][37][38][39][40][41][42], Campylobacter species [43][44][45], Staphylococcus aureus [46,47] and Escherichia coli [48] and [49].…”
Section: Resultsmentioning
confidence: 99%
“…Research addressing the issue of antibacterial resistant bacteria in Iraq includes many works in the recent years. Most researchers focused on bacterial species such as: Salmonella species [36][37][38][39][40][41][42], Campylobacter species [43][44][45], Staphylococcus aureus [46,47] and Escherichia coli [48] and [49].…”
Section: Resultsmentioning
confidence: 99%
“…Similarly, the stn genes were detected in 71.7% of the tested isolates in Egypt [ 24 ]. On the other hand, the stn gene could be detected in all Salmonella isolates [ 34 , 36 , 37 ]. In contrast,…”
Section: Discussionmentioning
confidence: 99%
“…Occurrence of NTS in raw milk in this study was higher than the occurrence reported by[20] who investigated that 6.66% of each market raw milk and bulk tank milk was contaminated by NTS. Also, lower occurrence was observed by[21] who isolated NTS from 3% (4 out of 133) of raw market milk samples but they failed to isolate Salmonella from milk samples collected directly from teat of lactating cows. On the other hand,[22] estimated higher occurrence (20.5%) of NTS in raw milk collected directly from the mammary gland during milking than in our study.…”
mentioning
confidence: 94%